Self-Medication and its associated factors among university students: A cross-sectional study - Anas Alomoush; Abdullah Alkhawaldeh; Mohamme ALBashtawy; Shaher Hamaideh; Wafa'a Ta'an; Raghad Abdelkader; Khitam Mohammad; Ahmad Rayan; Mohammad Alsadi; Omar Khraisat; Marah Shyab; Rasmieh Al-Amer; et al. (Wolters Kluwer Medknow Publications, 2024)
Background: Self-medication is a global concern among professionals and non-professionals, with a rapid increase in prevalence. The study aims to assess the prevalence of self-medication and its associated factors among university students. Materials and Methods: A cross-sectional, descriptive study was conducted in three universities, and a total of 817 college students participated in this study. Results: About 75.40% of the participants reported using medications without a professional prescription. The category of analgesics was the most commonly used in self-medication (82.80%), while the most common symptom was a headache (81.50%). Almost 74.10% percent of participants who have practiced self-medication stated that the reason was the "lack of time to consult a physician." Most participants who have used self-medication (90.30%) stated that the source of knowledge was "previous prescription." Conclusions: Health education programs concerning self-mediation should be held in university settings to improve attitudes and practices toward self-mediation.